Distribution of Phenol Derivatives by River Waters to the Marine Environment (Gulf of Gdansk, Baltic Sea) - Nehring Iga; Staniszewska Marta; Bodziach Karina (Oceanological and Hydrobiological Studies)
The aim of this study from 2020 was to identify the role of rivers, including those with low water flow and a constant inflow of bisphenol A (BPA), 4-tert-octylphenol (4-t-OP) and 4-nonylphenol (4-NP) to the marine environment. Water samples were collected from the small rivers flowing into the Gulf of Gdańsk and from the Vistula River. Final assays were performed using high-performance liquid chromatography with a fluorescence detector (HPLC-FL). The highest concentrations of phenol derivatives were found in summer, most likely due to higher consumption of products containing phenol derivatives. Another factor may be the type of development in the catchment area. The measurements did not exceed the PNEC, though this does not mean that the amounts of phenol derivatives introduced into the Gulf of Gdańsk by rivers can be ignored. Mean loads of xenobiotics introduced to the sea via rivers have been calculated as over 320 kg y−1 of BPA and about 55 kg y−1 of 4-t-OP and 4-NP each.